Moraxella catarrhalis Promotes Stable Polymicrobial Biofilms With the Major Otopathogens - Bair, Kirsten L.; Campagnari, Anthony A. (Frontiers in Microbiology, 2020)
Otitis media (OM) is a prevalent pediatric infection characterized by painful inflammation of the middle ear. The Gram-negative diplococcus Moraxella catarrhalis is a commensal of the nasopharynx and one of three leading causative agents of OM. The most recent work on this multifaceted disease indicates that biofilms and polymicrobial infections play a pivotal role in recurrent and chronic OM, which are difficult to eradicate using standard antibiotic protocols. Although there have been significant advances in OM research, the actual bacterial and viral interactions leading to pathogenesis remain largely uncharacterized. However, colonization and persistence in the nasopharynx is clearly an essential first step. In this study, we assessed the role M. catarrhalis plays in the co-colonization and persistence of the other major otopathogens, Streptococcus pneumoniae and non-typeable Haemophilus influenzae (NTHi). We characterized both monomicrobial and polymicrobial biofilms using an in vitro nasopharyngeal colonization model. Biofilm assays were designed to mimic the nasopharynx and bacterial persistence was quantified over time. NTHi showed a steady and significant decline in viability over 20 to 48 hours when this organism was in a dual species biofilm with S. pneumoniae. However, when M. catarrhalis was present in the polymicrobial biofilm NTHi survived for 48 hours at 107 CFU per mL. In addition, an isogenic M. catarrhalis catalase-deficient mutant was also fully capable of protecting NTHi from the bactericidal activity of S. pneumoniae in a polymicrobial biofilm. Our results show that M. catarrhalis promotes a favorable environment for stable polymicrobial biofilms by enhancing the survival of NTHi in the presence of S. pneumoniae. These data suggest that colonization with M. catarrhalis promotes stable co-colonization with other otopathogens.